Distribution pattern of the Zebra Mussel (Dreissena polymorpha) in White Bear Lake, Minnesota: a spatial scale analysis. Issue 1 (13th April 2023) - Hornbach, Daniel J.; Kozarek, Jessica L.; Blinick, Naomi; Hove, Mark C.; Grams, Paul; Kaplinski, Matt; MacGregor, Kelly R.; Milliren, Chris; Riesgraf, Andrew T.
Abstract: Zebra Mussels ( Dreissena polymorpha ) were introduced into the US in the 1980s and have since spread throughout the country with concomitant impacts on aquatic ecosystems. We placed 20 m transects in a variety of sediment types and collected data on sediment size, mussel coverage (the percent of the bottom covered by mussels), and the presence of macrophytes within 0.25 m 2 quadrats in White Bear Lake, MN. To assess the degree of Zebra Mussel aggregation, we calculated Morisita's index of dispersion (Iδ ) at four levels of spatial scale − 0.25 m 2, 1 m 2, 4 m 2, and 40 m 2 . Understanding the pattern of aggregation in Zebra Mussels is crucial in detecting early invasions, monitoring populations, and attempting to eradicate them. There was greater Zebra Mussel coverage within quadrats with coarser substrates (gravel/cobble and mixed sediment – including rock and boulders) compared to those with finer substrates (silt and sand). Macrophyte coverage did not significantly influence Zebra Mussel coverage on the lake bed sediments. Spatial scale had a large impact on the measure of mussel aggregation. Zebra Mussels in sand and silt had the highest degree of aggregation and high levels of macrophytes resulted in greater degrees of aggregation on the lake bed sediments. Zebra mussel coverage measured at larger spatial scales generally resulted in lower aggregation values, across both sediment types and levels of macrophyte coverage. The appropriate selection of spatial scale for sampling or observation is critical when upscaling local density to lake populations. KEY POLICY HIGHLIGHTS: Zebra Mussels have spread throughout the US and significantly alter aquatic ecosystems. Zebra mussels are often aggregated on the bottom of aquatic systems and are found preferentially on lake beds with coarser material at the bed (gravel and rock). Using the correct spatial scale to assess mussel coverage is crucial for accurate population estimates. Zebra Mussel infestations might be managed by partial-lake treatment options; however, treatment areas need to be chosen based on Zebra Mussel density and distribution patterns. Knowledge of the relationship between spatial scale, sediment type, macrophyte availability and population coverage and aggregation is needed for these types of treatment programs.